Following the Church Fathers: An Intertextual Path from Psalm 107 to Isaiah, Jonah, and Matthew 8:23–27 - Stone, Timothy J. (Journal of theological interpretation, 2013)
Can the history of interpretation inform and guide readings of Scriptures that have been neglected by that same tradition? Psalm 107 exemplifies one such neglected text. This article approaches the task by working within the presuppositions of precritical Christian theology and by following the many exegetical clues of precritical readers. On this foundation, I examine the pivotal role of Ps 107 within the shape of the Psalter; it marks the return from exile within the narrative arc of the collection. I continue to examine the exile in the structure of Ps 107, the four episodes of which illustrate the extent of the return from the four corners of the earth. Then I investigate the psalm's textual resonances with Isaiah and Jonah. Following the intertextual lead of precritical readers, I explore Jonah and Ps 107:23–32 in light of Matt 8:23–27 and its symbolic role in the Gospel of Matthew as a whole. I argue that the stilling of the storm is a preview to Jesus' death and resurrection. This adds an exegetical foundation to the varied use of the sign of Jonah by the Church Fathers. With them I agree that the sign of Jonah in Matthew refers to Jesus' death and resurrection. I conclude that Matt 8:23–27 serves as a lens through which Ps 107 and Jonah interpret the significance of Jesus' death and resurrection.